Daily Bible illustrations: being original readings for a year, on subjects from sacred history, biography, georgaphy, antiquities, and theology : Especially designed for the family circle - Kitto, John (R. Carter, 1850)
1. Antediluvians and patriarchs. 1850. -- 2. Moses and the Judges. 1860. -- 3. Samuel, Saul, and David. 1851. -- 4. Solomon and the kings. 1852. -- 5. Job and the poetical books. 1852. -- 6. Isaiah and the prophets. 1853. -- 7. The life and death of our Lord. 1853. -- 8. The Apostles and early church. 1854.